2020
DOI: 10.3390/nu12051496
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of an Early Lifestyle Intervention on Pregnancy Outcomes in a Cohort of Insulin-Resistant Overweight and Obese Women

Abstract: Obese women are more likely to have decreased insulin sensitivity and are at increased risk for many adverse pregnancy outcomes. An early lifestyle intervention (LI) may have the potential to reduce the impact of insulin resistance (IR) on perinatal outcomes. We report post hoc analysis of an open-label randomized control trial that includes IR women with body-mass index ≥25 randomly assigned to a LI with a customized low glycemic index diet or to standard care (SC) involving generic counseling about healthy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Among women with insulin resistance who are overweight or obese, a recent Italian randomized clinical trial (RCT) found that a lifestyle intervention beginning at 9 to 12 weeks’ gestation improved neonatal outcomes. 24 Ongoing HbA 1c control in the third trimester of pregnancy is also associated with a lower risk of perinatal mortality. 6 An additional clinically relevant finding is affirmation of the recommended periconceptional HbA 1c of less than 6.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Among women with insulin resistance who are overweight or obese, a recent Italian randomized clinical trial (RCT) found that a lifestyle intervention beginning at 9 to 12 weeks’ gestation improved neonatal outcomes. 24 Ongoing HbA 1c control in the third trimester of pregnancy is also associated with a lower risk of perinatal mortality. 6 An additional clinically relevant finding is affirmation of the recommended periconceptional HbA 1c of less than 6.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, also interpregnancy weight increase has found to be associated with LGA 33 . Therefore, we and others previously demonstrated that implementing an early customized low glycemic index, low fat diet together with the stimulation of physical activity has the potential to reduce the risk of LGA baby in some populations 34,35 . Unfortunately, quality, timing and adherence to intervention are factors signi cantly affecting success 42 .…”
Section: Discussionmentioning
confidence: 96%
“…One-on-one dietary counseling and an on-demand support system delivered by primary care personnel, even if coupled with limited adherence to physical activity and only modest weight loss after 6 months of lifestyle intervention, were more effective than standard care in improving glycaemic and cardiometabolic profiles in this target group [ 12 ]. The beneficial effects of an intensive lifestyle intervention, starting in early pregnancy and made of a calorie-restricted, low-glycemic-index, low-saturated-fat diet combined with moderate intensity physical activity (30 min of walking at least four days a week) were evaluated by Menichini and colleagues [ 14 ]. In obese singleton pregnant women with IR, this early intensive lifestyle intervention did not reduce the incidence rate of GDM with respect to standard care; however, mean glucose values at 75 g oral glucose tolerance test (OGTT), performed at 16–18 and/or 24–28 weeks of gestation in agreement with Italian guidelines, were significantly lower, as well as the birth rate of large-for-gestational-age (LGA) babies [ 14 ].…”
mentioning
confidence: 99%
“…The beneficial effects of an intensive lifestyle intervention, starting in early pregnancy and made of a calorie-restricted, low-glycemic-index, low-saturated-fat diet combined with moderate intensity physical activity (30 min of walking at least four days a week) were evaluated by Menichini and colleagues [ 14 ]. In obese singleton pregnant women with IR, this early intensive lifestyle intervention did not reduce the incidence rate of GDM with respect to standard care; however, mean glucose values at 75 g oral glucose tolerance test (OGTT), performed at 16–18 and/or 24–28 weeks of gestation in agreement with Italian guidelines, were significantly lower, as well as the birth rate of large-for-gestational-age (LGA) babies [ 14 ]. There is evidence that an excessive shunting of maternal nutrients across the placenta accelerates fetal growth and adipose tissue accretion from the early stages of pregnancy, and this increases the risk of macrosomia [ 15 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation